Studi sifat mekanis dan elektrik paduan Cu-Ni-Wx (2 ≤ x ≤ 5wt.%) disintesis menggunakan cold compaction - S. Suprianto; D. Hadiarsa; A. Syahputra; M. Mahadi; A. Pintoro (Universitas Mataram, 2024)
Copper-based alloys are common material which are widely used as electrodes for electrical discharge machining (EDM) due to their good electrical conductivity, but low mechanical properties. This problem can be solved by addition of some elements and also correct selected of the process parameter, in such compaction pressure in the powder metallurgy (PM) stages. The aim of this study to investigates the effect of W-refractory element and compaction pressure on the mechanical and electrical properties of the Cu-Ni-Wx based alloy. The research was conducted with varying (190, 220, and 250 MPa) of compaction pressure and Wx (x=2, 3, 4, and 5wt.%). Horizontal milling with 300 rpm has been used to mixing powder material. Furthermore, the sintering process at 770oC for 60 minutes by using a conventional furnace was conducted. In this current study, the maximum results of 123.2 VHN of the hardness, 325 MPa of compressive strength at 200 kN of the maximum load, and 4.62 x 107 (S/m) of the electrical conductivity were obtained at 250 MPa compaction pressure. The addition of W into Cu-based alloy tends to increase of the mechanical properties, however, reduce the electrical conductivity. On the other hand, microstructure observation shows that the increasing compaction pressure increases the solid solution phase between Cu-Ni and reduces the porosity.